P2.008 Mistaken Case of Child Abuse: A Case Report. (13th July 2013) - Sood, S; Verma, R; Mukherjee, A; Mahajan, N; Das, B K; Kapil, A; Gupta, S; Sharma, V K
Abstract : Introduction: The diagnosis of child abuse is based on a combination of child's history, physical findings, and when appropriate, laboratory and other tests. Overall, the diagnosis is often complicated but suspicion should always be followed by further investigations. Formulating a conclusion and reaching a diagnosis of child abuse may require the assistance and coming together of different specialities in the hospital. Case history: A seven year old girl presented to the Dermatology and Venereology OPD of a tertiary hospital in New Delhi, India with chief complaints of vaginal discharge for last 4 years. The vaginal swab(s) on Gram stain revealed numerous pus cells with GNDC, intracellular as well as extracellular. The child was treated based on clinical suspicion of gonorrhoea. However, RCUT put up from suspected colonies on modified Thayer Martin medium was positive for Neisseria meningitidis . In addition, crgA gene PCR from DNA extracted from the swab as well as the isolate was positive for N. meningitidis while opa -gene PCR for N. gonorrhoeae was negative . Although she was initially treated for suspected gonococcal infection, the clinical diagnosis was refuted by the results of culture and PCR. Discussion: & conclusion: The findings of the present case emphasise the importance of careful culture techniques for isolation of organisms & their correct identification which is the cornerstone of appropriate therapy. It also drives home the necessity of using lactose in Rapid Carbohydrate Utilization Test (RCUT), which is crucial to differentiate between N. meningitidis and N. lactamica. It is also important for the laboratory (especially one that is considered a referral laboratory) to have capacity to perform molecular tests to confirm or refute presumptive findings, as was done in the present case. This observation stresses that an interdisciplinary approach appears to be a valuable tool for evaluating such children.